Impaired nicotinamide adenine dinucleotide (NAD+) metabolism in diabetes and diabetic tissues: Implications for nicotinamide‐related compound treatment. Issue 6 (7th July 2020) - Fan, Lan; Cacicedo, Jose M.; Ido, Yasuo
Abstract: One of the biochemical abnormalities found in diabetic tissues is a decrease in the cytosolic oxidized to reduced forms of the nicotinamide adenine dinucleotide ratio (NAD + /NADH also known as pseudohypoxia) caused by oxidation of excessive substrates (glucose through the polyol pathway, free fatty acids and lactate). Subsequently, a decline in NAD + levels as a result of the activation of poly adenine nucleotide diphosphate‐ribose polymerase (mainly in type 1 diabetes) or the inhibition of adenine nucleotide monophosphate‐activated protein kinase (in type 2 diabetes). Thus, replenishment of NAD + levels by nicotinamide‐related compounds could be beneficial. However, these compounds also increase nicotinamide catabolites that cause oxidative stress. This is particularly troublesome for patients with diabetes, because they have impaired nicotinamide salvage pathway reactions at the level of nicotinamide phosphoribosyl transferase and phosphoribosyl pyrophosphate, which occurs by the following mechanisms. First, phosphoribosyl pyrophosphate synthesis from pentose phosphate pathway is compromised by a decrease in plasma thiamine and transketolase activity. Second, nicotinamide phosphoribosyl transferase expression is decreased because of reduced adenosine monophosphate‐activated protein kinase activity, which occurs in type 2 diabetes. The adenosine monophosphate‐activated protein kinase inhibition is caused by an activation of protein kinase C and D1 as a result of enhanced diacylglycerol synthesis caused by pseudohypoxia and increased fatty acids levels. In this regard, nicotinamide‐related compounds should be given with caution to treat diabetes. To minimize the risk and maximize the benefit, nicotinamide‐related compounds should be taken with insulin sensitizers (for type 2 diabetes), polyphenols, benfotiamine, acetyl‐L‐carnitine and aldose reductase inhibitors. The efficacy of these regimens can be monitored by measuring serum NAD + and urinary nicotinamide catabolites. Abstract : Diabetes causes nicotinamide adenine dinucleotide metabolism dysregulation characterized by increasing consumption of nicotinamide adenine dinucleotide to produce nicotinamide and decreasing conversion of nicotinamide to nicotinamide adenine dinucleotide (salvage cascade) by biochemical abnormalities, which have been postulated for the etiology of diabetic complications. This results in increasing production of nicotinamide catabolites, which might cause oxidative stress. For diabetes patients, nicotinamide‐related compounds, such as nicotinamide riboside and nicotinamide mononucleotide might be useful after correcting these abnormalities.